Ozone Improved Bone Dynamic of Female Rats Using Zoledronate - de Lima Neto, Tiburtino J. [UNESP]; Delanora, Leonardo Alan [UNESP]; de Sá Simon, Maria Eloise [UNESP]; Ribeiro, Kim Henderson Carmo [UNESP]; Matsumoto, Mariza Akie [UNESP]; Louzada, Mario Jefferson Quírino; Shibli, Jamil Awad; Ervolino, Edilson [UNESP]; Faverani, Leonardo P. [UNESP] (SAGE Publications, 2024)
The aim of this study was to analyze the effect of ozone (OZN) therapy on the dynamics of bone tissue in ovariectomized rats treated with zoledronic acid (ZOL). Female Wistar rats aged 6 months (n = 110) were subjected to bilateral ovariectomy (OVX). At month 3 post-OVX, 10 animals were euthanized to characterize the bone tissue architecture using microtomography (micro-CT). The remaining animals were divided into two groups: ZOL group, administered with ZOL (100 mg/kg body weight); saline (SAL) group (0.45 mL of SAL solution), both for 28 days. At month 3 post-treatment, 10 animals from each group were euthanized to characterize the bone architecture using micro-CT. The remaining animals were divided into the following groups: ZOL (n = 20), ZOL + OZN (n = 20); SAL (n = 20), and SAL + OZN (n = 20). The animals in ZOL + OZN and SAL + OZN groups were intraperitoneally administered with OZN (0.7 mg/kg body weight) once every 2 days. On days 30 and 60, six animals from each group were euthanized for analysis and structural characterization of bones in the femoral head and spine. Some samples of the femoral neck were subjected to biomechanical tests, while some samples were analyzed under a laser confocal microscope. The other samples collected from the femoral neck and spine were analyzed for area of neoformed bone and used for performing inflammatory cell and osteocyte counts. Data were submitted to statistical analysis considering a significance level of p < 0.05. Bone volume percentage and osteocyte and inflammatory cell counts were upregulated in the femoral head region of the ZOL + OZN group. Biomechanical analysis of the femoral neck revealed that the modulus of elasticity was similar between the ZOL and ZOL + OZN groups but differed significantly between the SAL and SAL + OZN groups. The positive areas for calcein and alizarin in the ZOL and ZOL + OZN groups were higher than those in the SAL and SAL + OZN groups. This suggested a positive synergistic effect of OZN and ZOL on the maintenance of bone mass and restoration of bone tissue vitality in ovariectomized rats.
Keywords: bone regeneration; osteoporosis; ozone